The role of mitochondrial functionality in brewing yeast - Moynihan, Eoin (2019)
Within yeast cell cultures typically 1-3% of the total cells contain damaged mitochondrial DNA (mtDNA). Damaged mtDNA manifests in the production of respiratory deficient ‘petite’ yeast cells. In certain circumstances such as in response to stress-inducing conditions associated with the modern brewing process the number of petites can exceed 10-20% of the total cell count. In order to provide insight into the formation of petites, this study aimed to analyse the mitochondria of several brewing yeast. The mitochondrial genotype was examined through sequencing and mtDNA fingerprints while the mitochondrial phenotype was examined using high resolution microscopy and flow cytometry. Interestingly, mtDNA fingerprinting revealed variation across S. cerevisiae strains, while conversely revealing little variation across S. pastorianus strains. Microscopy revealed some insight into the morphological variations of mitochondria, but flow cytometry yielded the greater insight into mitochondrial quantity and functionality. Additionally, changes in mitochondrial content throughout propagation, fermentation and storage were examined. With an understanding of the mitochondrial phenotype and genotype of respiratory competent ‘grande’, a comparative examination of the petite phenotype was undertaken. Genotypically and phenotypically the petites were shown to greatly differ to their grande counterparts, with less diverse mtDNA fingerprints and stunted mitochondrial morphology. Initial work was also undertaken to examine the impact of mitochondrial transfer from one species to another on yeast functionality.